The implementation and side effect management of immune checkpoint inhibitors in gynecologic oncology: a JAGO/NOGGO survey - Riedel, Maximilian; Herrmann, Helene; Bartl, Thomas; Rossner, Anna-Maria; Tatzber, Anna; Flethe, Chiara; Zocholl, Dario; Schmalfeldt, Barbara; Sehouli, Jalid; Pietzner, Klaus (BMC cancer, 2025)
The integration of immune checkpoint inhibitors (ICIs) into routine gynecologic cancer treatment requires a thorough understanding of how to manage immune-related adverse events (irAEs) to ensure patient safety. However, reports on real-world clinical experience in the management of ICIs in gynecologic oncology are very limited. The aim of this survey was to provide a real-world overview of the experiences and the current state of irAE management of ICIs in Germany, Switzerland, and Austria.
Gesehen am 02.10.2025